2022
DOI: 10.1155/2022/4052956
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal SWCC and Bimodal PSD of Soils with Dual-Porosity Structure

Abstract: The soil–water characteristic curve (SWCC) and pore-size distribution (PSD) are fundamental characteristics of soils that determine many physical and mechanical properties. Recent studies demonstrate that both SWCC and PSD sometimes exhibit a bimodal feature. In this paper, soils with bimodal SWCCs are mainly divided into three categories: gap-graded soils, compacted clayey soils, and natural dual-porosity structural soils, from the perspective of microporosity structure. Based on the Fredlund and Xing unimoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Thus, the relationship between PSD and SWCC is further investigated. Previous studies indicated that the MIP test is believed to be accurate in the low and medium suction range (i.e., medium and large pores) and is used in related studies to determine For water in the unsaturated soil, a similar relationship exists for matric suction s and pore diameter d, as shown by Equation (3).…”
Section: Comparison Of Measured and Psd-based Swccmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relationship between PSD and SWCC is further investigated. Previous studies indicated that the MIP test is believed to be accurate in the low and medium suction range (i.e., medium and large pores) and is used in related studies to determine For water in the unsaturated soil, a similar relationship exists for matric suction s and pore diameter d, as shown by Equation (3).…”
Section: Comparison Of Measured and Psd-based Swccmentioning
confidence: 99%
“…The soil-water characteristic curve (SWCC) is an essential relationship between soil suction and water content in unsaturated soils [1,2]. Besides the water retention capacity, SWCC could be used to investigate and predict several geotechnical properties of unsaturated soils, including the unsaturated shear strength [3][4][5][6][7], stress-strain relationship [8,9] and unsaturated permeability [10][11][12]. The SWCC of soils with different soil types and particle characteristics differs significantly.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of microscopic structure detection techniques, it was found that the pore structure of unsaturated soils could be influenced by the initial conditions, and thus affected the SWCC [18]. To obtain the pore structure information, two methods are commonly used: the scanning electronic microscope (SEM) and mercury intrusion porosimetry (MIP) [19,20]. Through MIP tests, the pore structure characteristic can be quantitatively obtained.…”
Section: Introductionmentioning
confidence: 99%